PENGARUH PENERBITAN SUKUK KORPORASI TERHADAP REAKSI PASAR MODAL INDONESIA PERIODE 2002-2016 - Fathima Dhiya Salsabilla; Hasbi Assidiki Mauluddi (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2017)
Abstract: The study aims to determine the prediction of differences that occur in capital market reactions before and after the issuance of sukuk, seen from the chances of trading volume activity and average abnormal return. The object of this study is a company that issued sukuk in the period of 2002-2016. The sample that taken for research is using purposive sampling technique. The method used in this research is comparative test analysis method with the observation period 14 days before the issuance of sukuk and 14 days after the issuance of sukuk. Sources of data used are secondary data in the form of historical stock prices derived from the Otoritas Jasa Keuangan and the Indonesia Stock Exchange. The results of this study based on different test results using wilcoxon signed rank test showedthat there was no significant changes in trading activity volume before and after the issuance of sukuk, proved by the significance of the test results of 0.887 bigger than the specified significance. Another test results using Paired Sample T-Test showed that there was no significant difference of abnormal return before and after issuance of sukuk, proved with significance of test result 0.913 bigger than the result of significance.Keywords: Sukuk Issuance, Trading Activity Volume, Abnormal Average Return